Need for Affect in Romantic Relationships - Huić, Aleksandra; Jugović, Ivana; Huston, Ted; Kamenov, Željka (2010)
Need for affect is defined as a general motivation to approach or avoid emotion-inducing situations. This study examined whether the need for affect plays a significant role in relationships. Using a sample of 500 married couples, our aim was to investigate (1) the overall effect of need for affect ; (2) whether particular combinations of need for affect (e.g., both spouses high ; one spouse high, the other low) produce distinct behavioral dynamics ; and (3) how need for affect and behavioral dynamics, when considered together, are associated with spouses’satisfaction with marriage. We expect couples with higher levels of need for affect to have more intense relationships. Also, relationships where both partners have similar need for affect levels should be more satisfactory than relationships where one partner has a high, and the other a low approach/avoid motivation. We also hypothesized that, depending on these similarities, couples will differ in actual affectionate, antagonistic, and sexual behaviors they exhibit, and the way they show love to their spouse. We administered The Need for Affect Scale, The Love Scale, and asked participants about the ways they show love, their specific behaviors in this relationship, and their marital satisfaction. Our findings show how the spouses’ need for affect, considered in tandem, is associated both with how well they feel and get along with each other, as well as how they feel about their relationship.
Projekt MZOS
ENG